ST3Gal IV Mediates the Growth and Proliferation of Cervical Cancer Cells In Vitro and In Vivo Via the Notch/p21/CDKs Pathway - Wu, Yinshuang; Chen, Xixi; Dong, Weijie; Xu, Zhongyang; Jian, Yuli; Xu, Chunyan; Zhang, Lin; Wei, Anwen; Yu, Xiao; Wang, Shidan; Wang, Yue; Liu, Gang; et al. (Frontiers in Oncology, 2021)
ST3Gal IV is one of the principal sialyltransferases responsible for the biosynthesis of α2, 3-sialic acid to the termini N-glycans or O-glycans of glycoproteins and glycolipids. It has been reported that ST3Gal IV expression is associated with gastric carcinoma, pancreatic adenocarcinoma and breast cancer. While the expression and functions of ST3Gal IV in cervical cancer are still poorly understood. In this study, we found that ST3Gal IV was downregulated in human cervical cancer tissues compared to normal cervix tissues, and ST3Gal IV expression was negatively associated with the pathological grade of cervical cancer. ST3Gal IV upregulation inhibited the growth and proliferation of cervical cancer HeLa and SiHa cells in vitro and in vivo. Furthermore, ST3Gal IV overexpression enhanced the expression of several Notch pathway components such as Jagged1, Notch1, Hes1 and Hey1, while cell cycle protein expression like Cyclin D1, Cyclin E1, CDK2 and CDK4 were decreased. These results indicate that expression of ST3Gal IV is reduced in cervical cancer and plays a negative role in cell proliferation via Notch/p21/CDKs signaling pathway. Thus, sialyltransferase ST3Gal IV might be a target for the diagnosis and therapy of cervical cancer.